Effect of light and shade on performance of different grass species in sub-tropical conditions of Jammu - Namgial, Jigmet; Dr. S.K. Gupta; Dr. B.C. Sharma; Dr. Meenakshi Gupta; Dr. Vikas Abrol; Dr. Manish Shrama (Indian Journal of Agroforestry, 2025)
A study was carried out from 2021 to 2023 at the Experimental Farm of Division of Silviculture and Agroforestry, Chatha, SKUAST – Jammu (J&K). The experiment included 7 treatments (grass species): T1- Setaria anceps (var. S-25), T2 - Sorghum bicolor, T3 - Setaria anceps (var. PSS-1), T4 - Pennisetum purpureum, T5 - Paspalum notatum, T6 - Bracharia decumbens and T7 - Natural grass grown under the shade of Terminalia chebula trees as well as in open conditions i.e., tree-less plots. The experimental trial was laid out using Randomized Block Design with 3 replications. Results indicated that values of growth parameters such as plant height, leaf length, and leaf area were higher when grass species were grown under the trees compared to open conditions. Specifically, T2 (Sorghum bicolor) exhibited maximum plant height, leaf length, and leaf area under shaded conditions. Conversely, the number of tillers and leaves per plant were recorded higher under open conditions, with T3 (Setaria anceps, var. PSS-1) showing the highest values among all grass species. Yield parameters including fresh and dry forage yield, were significantly higher in open conditions compared to those under the shade of Terminalia chebula trees consistently during the study period. Among all the grass species, T3 (Setaria anceps var. PSS-1) exhibited the maximum fresh and dry forage yield under open conditions.